Analisis Prioritas Solusi Permasalahan Pengelolaan Wakaf Produktif (Studi Kasus Kabupaten Banjarnegara) - Resfa Fitri; Heni P Wilantoro (Department of Islamic Economics, IPB University, 2018)
Waqf is one of the instruments in Islamic economics that can be used for development funding. In addition, waqf is also very potential to improve people’s welfare. In essence, the waqf is a matter that should be productively managed as contained in the hadith. However, it is currently in the opposite state. This study analyzes the priority of problems and solutions to optimize the management of waqf assets in Banjarnegara Regency, one of regencies in Central Java with highest poverty rate. Analytic Network Process (ANP) is the method used in this study. The result of the research shows that the main priority of human resource problem is the low managerial ability of the nazhir. The priority of institutional problem is the role of BWI Banjarnegara that is not yet optimal, while the priority of the government problem is the lack of support and role of the government. The priority solution of the most important problem is coaching and mentoring for nazhir.